Strategi Ustaz Dalam Mengajarkan Baca Al-Qur’an Melalui Metode Tahsin di TPA Al-Hishnul Mubarok Desa Pakkasalo - Nurul Syahira; Aminullah; Sadali (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2025)
Optimal Qur'an learning can produce a Qur'anic generation, namely a generation that is not only proficient in reading, but also able to apply Qur'anic values ​​in prospering the earth and building civilization. This study uses a descriptive qualitative approach that aims to understand the phenomenon of tahsin learning of the Qur'an comprehensively. Qualitative research was chosen because of its ability to explore the behavior, perceptions, and motivations of research subjects through in-depth descriptions of words. The tahsin learning strategy at TPA Al-Hishnul Mubarok is designed systematically and responsively to the needs of students. Ustaz sets goals that are in accordance with abilities, delivers material in stages, applies talaqqi, tadarus, and direct correction methods, and utilizes media such as tajwid mushaf, qari audio, whiteboard, and Android TV. Evaluation is carried out through oral and written tests, and practical observations.